2007
DOI: 10.1073/pnas.0701051104
|View full text |Cite
|
Sign up to set email alerts
|

Design of protein–membrane interaction inhibitors by virtual ligand screening, proof of concept with the C2 domain of factor V

Abstract: Most orally bioavailable drugs on the market are competitive inhibitors of catalytic sites, but a significant number of targets remain undrugged, because their molecular functions are believed to be inaccessible to drug-like molecules. This observation specifically applies to the development of small-molecule inhibitors of macromolecular interactions such as protein-membrane interactions that have been essentially neglected thus far. Nonetheless, many proteins containing a membrane-targeting domain play a cruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 45 publications
0
68
0
Order By: Relevance
“…Removal of TM may destabilize the protein-membrane interaction, thus affecting moenomycin or lipid II binding to TG. Indeed, stable proteinmembrane interaction has been reported recently to be crucial for the normal function of some membrane proteins, and hence it has been suggested to be a target for drug discovery (24).…”
Section: Resultsmentioning
confidence: 99%
“…Removal of TM may destabilize the protein-membrane interaction, thus affecting moenomycin or lipid II binding to TG. Indeed, stable proteinmembrane interaction has been reported recently to be crucial for the normal function of some membrane proteins, and hence it has been suggested to be a target for drug discovery (24).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, there are a number of cases where a disease is attributable to the abrogation of these properties (22) (23). Bioinformatics and computational biology have also begun to play a major role in lipid-binding domain studies, eliciting predictions of potential lipid-binding proteins (24), the role of electrostatics in lipid binding (25), and assembly of databases that compile lipid-binding domain data and predictions of membrane binding properties (26,27).…”
Section: : S299-s304mentioning
confidence: 99%
“…A number of small organic molecules were identified that disrupt C2 domain membrane anchoring of FVIII (14) and FV (15). One of these inhibitors, 005B10, identified from in silico screening, was found to inhibit FVIII interaction with negatively charged phospholipids (15).…”
Section: Blood Coagulation Factor VIII (Fviii)mentioning
confidence: 99%
“…, that interferes with C2 domain membrane binding was identified by Segers et al (15) using a computational approach. This compound inhibited membrane binding of FVIII with an IC 50 of 7.8 M, as measured by surface plasmon resonance (Fig.…”
Section: The Structure Of the C2 Domain-inhibitor Complex And The Inhmentioning
confidence: 99%
See 1 more Smart Citation